A CGG‐Repeat Expansion Mutation in ZNF713 Causes FRA7A: Association with Autistic Spectrum Disorder in Two Families. Issue 11 (November 2014) - Metsu, Sofie; Rainger, Jacqueline K.; Debacker, Kim; Bernhard, Birgitta; Rooms, Liesbeth; Grafodatskaya, Daria; Weksberg, Rosanna; Fombonne, Eric; Taylor, Martin S.; Scherer, Stephen W.; Kooy, R. Frank; FitzPatrick, David R.
ABSTRACT We report de novo occurrence of the 7p11.2 folate‐sensitive fragile site FRA7A in a male with an autistic spectrum disorder (ASD) due to a CGG‐repeat expansion mutation (∼450 repeats) in a 5′ intron of ZNF713. This expanded allele showed hypermethylation of the adjacent CpG island with reduced ZNF713 expression observed in a proband‐derived lymphoblastoid cell line (LCL). His unaffected mother carried an unmethylated premutation (85 repeats). This CGG‐repeat showed length polymorphism in control samples (five to 22 repeats). In a second unrelated family, three siblings with ASD and their unaffected father were found to carry FRA7A premutations, which were partially or mosaically methylated. In one of the affected siblings, mitotic instability of the premutation was observed. ZNF713 expression in LCLs in this family was increased in three of these four premutation carriers. A firm link cannot yet be established between ASD and the repeat expansion mutation but plausible pathogenic mechanisms are discussed.